Developing Maqasid al-Shariah-Based Artificial Intelligence Models for Transformative Islamic Education in the Era of Technological Disruption and Knowledge Society - Uria Hasnan; Muhammad Eissawy Abu El Yazid; Abubaker Kashada; Mohammad Ahmad Bani Amer; Rahmat Ullah; Ahmad Faizal Syahrul Azmi (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to develop a novel conceptual framework for Artificial Intelligence based on Maqasid al-Shariah in the context of transforming Islamic education amid technological disruption and the knowledge society. Employing a qualitative approach through library research, the study critically analyzes classical and contemporary literature on Islamic education, artificial intelligence, and Maqasid al-Shariah theory. The novelty of this research lies in the integrative construction of a Maqasid-based AI model that systematically embeds the five essential protections religion, intellect, life, lineage, and wealth into the architecture of educational technology design, moving beyond conventional AI applications that are predominantly technical and value-neutral. The findings demonstrate that AI integration in Islamic education must be normatively guided to ensure alignment with ethical, spiritual, and epistemological principles of Islam. Furthermore, this study introduces a maqasid-driven evaluative and operational framework that not only enhances learning efficiency but also actively fosters spiritual formation, moral integrity, and intellectual development. Unlike prior studies that treat ethics as an external constraint, this research positions Maqasid al-Shariah as an intrinsic design principle within AI systems. The study also identifies critical risks of unregulated AI adoption, including doctrinal distortion, cognitive dependency, privacy violations, moral decline, and excessive commercialization of education. Therefore, it proposes a collaborative and interdisciplinary AI design model involving technologists, educators, and Islamic scholars to ensure value-driven innovation.